Innovative Practices and Research in Theatrical and Film Art Design - Pu, Xiaodi; Huang, Chaoyu; Wu, Siyu (Transactions on Social Science, Education and Humanities Research, 2024)
This paper explores innovative practices in theatrical and film art design, analyzing how these practices integrate artistic expression with technological advancements. Through literature review and empirical analysis, we focus on case studies in film production and stage design to examine the application of modern technologies in artistic design and their impact on creative innovation. The study reveals that innovative practices not only expand the boundaries of art design but also enhance emotional connections between audiences and productions. Finally, the paper outlines future research directions and technological trends in this field.